2024
DOI: 10.3390/app14020912
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Application of a Deep Learning-Based Primary Support Deformation Prediction Model for Large Cross-Section Tunnels

Junling Zhang,
Min Mei,
Jun Wang
et al.

Abstract: The deformation of tunnel support structures during tunnel construction is influenced by geological factors, geometrical factors, support factors, and construction factors. Accurate prediction of tunnel support structure deformation is crucial for engineering safety and optimizing support parameters. Traditional methods for tunnel deformation prediction have often relied on numerical simulations and model experiments, which may not always meet the time-sensitive requirements. In this study, we propose a fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…D Martinelli et al [24] demonstrated the applicability of the tunnel model under different stress conditions through the discrete element method. Zhang et al [25] proposed a fusion deep neural network (FDNN) model to evaluate the most important influencing factors on tunnel deformation. Li et al [26] simulated the impact of super-large-diameter shield tunnel on the displacement of existing tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…D Martinelli et al [24] demonstrated the applicability of the tunnel model under different stress conditions through the discrete element method. Zhang et al [25] proposed a fusion deep neural network (FDNN) model to evaluate the most important influencing factors on tunnel deformation. Li et al [26] simulated the impact of super-large-diameter shield tunnel on the displacement of existing tunnel.…”
Section: Introductionmentioning
confidence: 99%